Pomalidomide in Combination with Low-Dose Dexamethasone as the Treatment of “Double Refractory” Multiple Myeloma - AV Petrov; DV Motorin; OS Pokrovskaya; ES Urnova; MV Nareiko; DV Babenetskaya; YuA Alekseeva; LL Girshova; LP Mendeleeva; AYu Zaritskii (Клиническая онкогематология)
Background. The development of radical therapy for multiple myeloma (MM) is still a pressing problem. This progressive disease requires repeated courses of therapy using drugs without cross-resistance. The prognosis of “double refractory” MM which is resistant to key antitumor drugs, first generation protease inhibitors and immunomodulating agents, remains poor. The median progression-free survival (PFS) and overall survival (OS) in this cohort of patients are 5 and 9 months, respectively.